Analysis of Internal Audit, Audit Committee, and Board of Commissioners on the Quality of Financial Report Disclosure - Suparlan, Suparlan; Dewi Masitah; SettingsLulu Ilmang Suro; Andini Melinia Sari (Cita konsultindo, 2024)
The quality of financial report disclosure refers to the extent to which financial information is presented in a timely, transparent, accurate, and complete manner to meet the needs of stakeholders, including investors, regulatory authorities, and the public. Empirical studies show that the effectiveness of internal audits, audit committees, and boards of commissioners plays a crucial role in determining the quality of financial report disclosure. This is particularly relevant in the context of banking companies, which face challenges related to regulations, transaction complexity, and public trust. This research used data from 47 banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The research method employed multiple linear regression analysis. The results show that the number of internal audit members, audit committee members, and board of commissioner members has a significant impact on the quality of financial reports, as reflected in the number of pages in the annual report.